PERANCANGAN ALAT PENGINGAT, BAK SEMAI DAN PANDUAN UNTUK PERTANIAN ORGANIK - Vanessa Natalia Ayu C.; Wyna Herdiana; Tuani Lidiawati Simangunsong (CALYPTRA, 2018)
Organic farming collects all the imagination of farmers and consumers seriously and is responsible for avoiding chemicals and fertilizers that are toxic to the environment, in order to obtain healthy environmental conditions. In this study raised the concept of organic farming so that farmers who still use conventional ways easier and interested to switch to organic methods. The purpose of this research is to create a set of tools that facilitate the farmers in controlling the production process, so that production becomes more stable and value-added.The method used in this research is qualitative method of observation, in depth interview, and focus group discussion. Based on the observations, it is known that the farmers are traditional farmers, so they are still based on the constellation and the climate where it is not applicable due to climate change, then the absence of good means of information and reminder to assist the population in controlling the stages of planting, fertilization and so on.This research produces a series of tools, applied to the learning process of traditional farmers with a cubism design developed in 1910-1914.The design focuses on the simplification of geometric forms of nature, in which the flow arises from the appearance of boredom of classical streams full of ornaments.